Interprofessional education program administration: the key to collaborative, successful and sustainable pre-registration IPE programs. - Wickramasinghe, Udara; Symes, Ashley; McKinlay, Eileen (Journal of Interprofessional Care)
Interprofessional education (IPE) struggles to be sustainable in many educational institutions, whether it adopts a centralized or decentralized model of implementation, and IPE programs sometimes do not endure. One reason for this may be the considerable burden that complex coordination of IPE can place on academic faculty with insufficient, or absent, support staff with the necessary complementary administrative skills. This discussion article contends that the role of support administrators is pivotal in operationalizing IPE. IPE support administrators, who are staff with advanced administration skills, add value to faculty efforts in a cost-effective way, thus maximizing the possibility of delivering high-quality, sustainable IPE programs. We identify seven core areas of focus for IPE support administration and illustrate their application in three case studies, with the aim of identifying effective principles and practices for other institutions as they operationalize IPE and keep it practical and financially sustainable.